Diagnosis, Management and Assessment of Adults with Joint Hypermobility Syndrome: A UK‐Wide Survey of Physiotherapy Practice. (18th March 2015) - Palmer, Shea; Cramp, Fiona; Lewis, Rachel; Muhammad, Shahid; Clark, Emma
Abstract Joint hypermobility syndrome (JHS) is a heritable disorder associated with excessive joint range of motion and pain in the absence of inflammatory joint disease. It is a relatively common cause of musculoskeletal pain but is generally understood to be under‐recognized and poorly managed in clinical practice. The present study therefore aimed to identify how JHS is diagnosed, managed and assessed in routine physiotherapy practice. A survey tool was developed from similar physiotherapy surveys of musculoskeletal practice, a review of the literature, and consultation with researchers and clinicians. Paper copies of the final survey were sent to 201 randomly selected secondary care organizations across the UK and an electronic version was advertised through physiotherapy professional networks. A total of 66 responses (80% women) were received from physiotherapists, with a wide range of clinical experience. Only 32% of respondents reported that they had received formal training in JHS management. The Brighton diagnostic criteria for JHS were not often used (only 31% of respondents). The stated aims of physiotherapy and the specific interventions employed seem well matched, with a focus on advice, education, exercise and self‐management. Although pain relief was not reported as a high priority in terms of treatment aims, pain was most often assessed as an outcome, suggesting a mismatch between what clinicians aim to achieve and what they measure. The results suggest that reported management strategies are broadly appropriate to long‐term musculoskeletal conditions but additional training specific to JHS may be required, particularly in diagnosis and assessment. Copyright © 2015 John Wiley & Sons, Ltd.